The JARANAN TURONGGO YAKSO DONGKO DISTRICT TRENGGALEK DISTRICT IN AN ETHNOGRAPHIC APPROACH: JARANAN TURONGGO YAKSO DONGKO DISTRICT TRENGGALEK DISTRICT IN AN ETHNOGRAPHIC APPROACH - Jaya, Rhesa; Sugito, Bambang (Solah, 2025)
Jaranan Turonngo Yakso is an art form originating from Trenggalek Regency in 1976 and created by Mr. Pamrihanto. This study focuses on understanding the art of Turonggo Yakso which is influenced by several daily behaviors in the lives of the people surrounding the art. This study is a qualitative descriptive study with research data in the form of sentences containing the ethnography of Turonggo Yakso. The purpose of this study is to describe Jaranan Turonggo Yakso in an ethnographic approach. Data in this study were collected using observation, interview, and documentation methods. Research data were analyzed using data reduction and data presentation. Based on the data analysis, it was found that Jaranan Turonggo Yakso is one of the series in the culture of the Baritan traditional ritual community (bubar ngarit tanduran) in Dongko District, Trenggalek Regency. The Jaranan Turonggo Yakso dance visualizes the activities and ethnicities of the people of Trenggalek Regency who work as farmers, so that the composition of various movements is the activity of farmers going to the rice fields then experiencing problems until returning home. The local values inherent in and inseparable from the cultural traditions of the Dongko District community in Trenggalek Regency. The selection of materials, motifs, and clothing styles incorporates local values found in Dongko District, Trenggalek Regency. The musical accompaniment also includes a special instrument, the kereg, made from bamboo, which produces the "kreg krog kreg" sound. Keywords: Baritan, Turonggo Yakso, Ethnography